2020
DOI: 10.1186/s12889-020-09836-6
|View full text |Cite|
|
Sign up to set email alerts
|

Improving lifestyles sustainability through community gardening: results and lessons learnt from the JArDinS quasi-experimental study

Abstract: Background Despite an increasing number of studies highlighting the health benefits of community gardening, the literature is limited by cross-sectional designs. The “JArDinS” quasi-experimental study aimed to assess the impact of community garden participation on the adoption of more sustainable lifestyles among French adults. Methods Individuals entering a community garden in Montpellier (France) in 2018 (n = 66) were compared with pairwise match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
30

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 59 publications
(77 reference statements)
0
11
0
30
Order By: Relevance
“…While the results of the US study are yet not available, those of the French have just been published. 58 This quasiexperimental study found no positive impact of the first year of community gardening on healthiness of household's food supplies, physical activity, BMI, mental well-being and social health, connection to nature, sensibility to food waste, as well as, the environmental impact and expenditure of food purchased. Qualitative interviews revealed several barriers to the participation such as lack of time, lack of gardening knowledge, physical difficulty of gardening, health problems and conflicts with other gardeners, possibly explaining the lack of impact and confirming the importance of mixing quantitative and qualitative approaches in intervention research studies.…”
Section: Discussionmentioning
confidence: 74%
“…While the results of the US study are yet not available, those of the French have just been published. 58 This quasiexperimental study found no positive impact of the first year of community gardening on healthiness of household's food supplies, physical activity, BMI, mental well-being and social health, connection to nature, sensibility to food waste, as well as, the environmental impact and expenditure of food purchased. Qualitative interviews revealed several barriers to the participation such as lack of time, lack of gardening knowledge, physical difficulty of gardening, health problems and conflicts with other gardeners, possibly explaining the lack of impact and confirming the importance of mixing quantitative and qualitative approaches in intervention research studies.…”
Section: Discussionmentioning
confidence: 74%
“…Community gardens have been proven to play an important role in the socialecological resilience of urban ecosystems and offer residents a place where they can reduce stress, share experiences, and gain community support [119,120]. Previous research has shown that community gardens provide a model that can promote sustainable urban living by linking individuals and communities to the food system and promoting the development of a deep reconnection and long-term commitment to sustainable living practices [84,85,121,122]. It has been concluded that the aesthetic value of urban gardens helps enhance the attractiveness of urban areas and that a scientific garden distribution is more likely to contribute to a larger network of ecosystem services across a broader urban landscape [123][124][125].…”
Section: Discussionmentioning
confidence: 99%
“…The 'exposure-effect' of urban gardening on health and well-being has been largely investigated [14][15][16][17][18].Available studies have shown that the incidence of various chronic and non-communicable diseases, including depression and anxiety symptoms, diabetes, and obesity, is affected by the availability and size of green spaces [19].…”
Section: What Is the Link Between Human Health And Well-being And Commentioning
confidence: 99%